1991
DOI: 10.1159/000204863
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Arachidonic Acid Metabolites from Stimulated Whole Blood in Patients with Chronic Myeloproliferative Disorders

Abstract: We have evaluated the arachidonic acid (AA) metabolism in patients with myeloproliferative disorders (MPD). In essential thrombocythemia (ET), the generation of thromboxane B2 was found significantly reduced and inversely correlated with platelet count. Polycythemia vera (PV) patients showed an increased formation of this metabolite of AA. Prostaglandin E2 and 6-keto-PGF generation were markedly reduced in patients with chronic myelogenous leukemia. Our study confirms that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In addition, targeted therapies against specific enzymes or metabolites of the AA metabolism pathway may be beneficial in AMS prevention and demand further studies (Atluri et al, 2011 ). Given its close relationship with hemoglobin metabolism genes, the AA metabolism pathway may be an effective target for the prevention of hypoxia-induced erythrocytosis (Foley et al, 1978 ; Parise et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, targeted therapies against specific enzymes or metabolites of the AA metabolism pathway may be beneficial in AMS prevention and demand further studies (Atluri et al, 2011 ). Given its close relationship with hemoglobin metabolism genes, the AA metabolism pathway may be an effective target for the prevention of hypoxia-induced erythrocytosis (Foley et al, 1978 ; Parise et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since our tissue culture medium contains serum albumin, it might be contributing to the absence of PGD 2 in our analysis. Previous studies have suggested that PGE 2 is reduced in CML patients [61]; hence, this may be why our method was unable to detect PGE 2 in samples. Upon IFN treatment, intracellular production of 5-HETE appears to be maintained, possibly through metabolism from AA, or by the reduction of 5-oxo-ETE (and NADP+) to 5-HETE (and NADPH) [57].…”
Section: Discussionmentioning
confidence: 79%
“…Since our tissue culture media contains serum albumin, it might be contributing to the absence of PGD2 in our analysis. Previous studies have suggested that PGE2 is reduced in CML patients [64], hence this may be why our method was unable to detect PGE2 in samples. Upon IFN-treatment, intracellular production of 5-HETE appears to be maintained, possibly through metabolism from AA, or by the reduction of 5-oxo-ETE (and NADP+) to 5-HETE (and NADPH) [60].…”
Section: Discussionmentioning
confidence: 84%